INTERPRETATION OF JUSTICE IN THE MEMORABLE STORY OF GHAFUR GHULAM (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article analyzes the fate of a person described in the story “The Stranger” by Ghafur Ghulam, the issues of ensuring justice and the analysis of the images in the work, and the strength of the Ghafur Ghulam fist.